Influence of Bio-Enzyme on Strength Characteristics of Soil - P. Ravi Kumar, G. Anil Kumar, R. Mallikarjun Rao, K.Chaitanya, K. Sireesha, K. Krishna Chaitanya (International Journal of Advanced Science and Technology, 2020)
There is requirement of developing new techniques in countries like India to increase performance and economical feasibility of soil. This paper defines the usage of bio-enzyme in soil stabilisation process. One of the most widely used bio-enzyme is TerraZyme; bio-enzyme usage is an eco-friendly practice. In this study TerraZyme is added to soil in 4 dosages. Strength and stability tests on soils are conducted to check the performance of TerraZyme based soil. Comparison also evaluated between normal and TerraZyme based soil.